2019
DOI: 10.17533/udea.redin.20190521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of DC optimizers on photovoltaic production

Abstract: Energy efficiency is a key element in the Smart Cities (SC), in which integration of renewable sources is a reality. Small-scale integration is usually implemented with photovoltaic (PV) and solar thermal energy. The shadows on the PV modules are a reality as they are originated by unavoidable buildings and obstacles existing in the cities. These shadows will cause the decrease in PV efficiency. Therefore, the increase in PV efficiency is essential. This increase in efficiency can be achieved by associating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…While MLPE were designed to recover the power loss from panel mismatch, the string or centralized inverter was not designed to recover the power loss from panel mismatch, so the comparison between PV systems using MPLE and PV systems using a string or centralized inverter under PSC seems unfair. Finally, Figure 8 summarizes the difference between our study and other existing studies [12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…While MLPE were designed to recover the power loss from panel mismatch, the string or centralized inverter was not designed to recover the power loss from panel mismatch, so the comparison between PV systems using MPLE and PV systems using a string or centralized inverter under PSC seems unfair. Finally, Figure 8 summarizes the difference between our study and other existing studies [12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 84%
“…However, more studies are required to verify the ability of improving the energy harvested from PV systems under PSC. While other studies in the literature [12][13][14][15][16][17][18][19] have shown the advantage of using MLPE (microinverter or DC optimizer) over the string or centralized inverter under partial shading conditions and in nonshading conditions, the energy performance of a string or centralized inverter is shown to outperform MLPE (especially when the string or centralized inverter is integrated with MPPT (maximum power point tracking)), our study revealed for the first time, (while, to the extent of our knowledge, the past literature did not), that MLPE did not effectively improve the energy harvested from PVs under PSC compared with that in NSC. While MLPE were designed to recover the power loss from panel mismatch, the string or centralized inverter was not designed to recover the power loss from panel mismatch, so the comparison between PV systems using MPLE and PV systems using a string or centralized inverter under PSC seems unfair.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation